XRF scanner data (Si, Ca, Al, Fe, K, Ti, Ba, Sr) and calibrated high resolution element concentrations for sediment core PS58/270-5 - Struve, Torben; Lamy, Frank; Gäng, Frederik; Klages, Johann Philipp; Kuhn, Gerhard; Esper, Oliver; Lembke-Jene, Lester; Winckler, Gisela (In: Struve, T et al. (2025): Sediment composition and particle flux reconstructions for the Southeast Pacific Antarctic Zone [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.982690, 2025)
This dataset contains XRF-scanner data for core PS58/270-5 collected during R/V Polarstern expedition ANT-XVIII/5a in 2001 (Miller, 2001) in the South Pacific Antarctic Zone (62.028°S, 116.123°W; 4981 m water depth). The XRF-scanner data were used in combination with element concentrations (doi:10.1594/PANGAEA.983125) derived from discrete sample digests to produce high resolution downcore records for PS58/270-5. The reported age model is derived from diatom-based stratigraphy and correlation of SSSTs and Fe content with EDC ice core data (doi:10.1594/PANGAEA.983158). This dataset uses a revised stratigraphy as section 1995-2095 cm was curated in reverse order.
Keywords: glacial-interglacial changes; iron fertilization; particle fluxes; Pleistocene; Southern Ocean; WAIS